Role of Combined Mifepristone and Misoprostol Verses Misoprostol Alone in Induction of Labour in Patients with Intrauterine Foetal Death - a Randomized Comparison Between their Outcome (Anwer Khan Modern Medical College Journal, 2017)
Background: Intrauterine fetal death is means- intrapartum death after the fetus has reached the age of viability8. As in IUFD journey, labor pain will be fruitless. So, it is of utmost importance to search for the method which can reduce hours of pain in labor of IUFD cases.Metarials Methods: In this research work patients divided in two groups. Induction of labour in one group was given by combination of mifepristone and misoprostol other group by misoprostol only and we try to find out the best method. To compare the effectiveness, induction to delivery interval, safety and side effects of combination of mifepristone and misoprostol versus conventional use of misoprostol alone in induction of labour in patients with intrauterine fetal death. It is a Prospective randomized comparative study in Anwer Khan Modern Medical College Hospital and Dhaka Medical College Hospital among 70 patients with IUFD after 28 weeks of gestation during January 2014- January 2016.Result: We allowed the patients up to third gravid and after 28 weeks of gestation. Patients were grouped as Group A(35) & Group B (35). In Group A Induction was given by single oral dose of 200 mg mifepristone, and after 48 hours, tab. Misoprostol in post. fornix started if 34 weeks-50 ?gm dose. Doses were repeated every 6 hourly intervals if required. In Group B Induction was given by 100 ?gm misoprostol at 6 hourly interval in post. Fornix. In both groups we allowed misoprostol maximum 600 ?gm. Oxytocin was given for augmentation if needed. The two study groups did not differ demographically. Induction to delivery time was shorter with combined regimen group (P